2003
DOI: 10.1124/jpet.103.054510
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Modeling of the Pharmacodynamic Interaction of Alphaxalone and Midazolam in Rats

Abstract: The objective of the present investigation was to characterize the pharmacodynamic interaction between the synthetic neuroactive steroid alphaxalone and the benzodiazepine midazolam. The time course of the electroencephalographic (EEG) effect (11.5-30 Hz) was determined in rats in conjunction with plasma concentrations. Alphaxalone was administered as a continuous intravenous infusion of 0, 1.2, 2.2, or 5.2 mg over 360 min. Midazolam was administered as a 5-min intravenous bolus infusion of 4 mg⅐kg Ϫ1 . The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This is consistent with our data indicating that midazolam does not undergo significant intestinal first-pass metabolism during oral absorption in rats. The systemic clearance reported in our chronic animals is in the range reported by others (Cleton et al, 1998;Visser et al, 2003) and indicates that midazolam is an "intermediate" clearance drug. As such, alterations in systemic clearance would therefore reflect changes in either organ blood flow or CYP3A activity or both (Pang and Rowland, 1977).…”
Section: Tablesupporting
confidence: 85%
“…This is consistent with our data indicating that midazolam does not undergo significant intestinal first-pass metabolism during oral absorption in rats. The systemic clearance reported in our chronic animals is in the range reported by others (Cleton et al, 1998;Visser et al, 2003) and indicates that midazolam is an "intermediate" clearance drug. As such, alterations in systemic clearance would therefore reflect changes in either organ blood flow or CYP3A activity or both (Pang and Rowland, 1977).…”
Section: Tablesupporting
confidence: 85%
“…(2008) found that butorphanol administered to foals at 0.05 mg kg −1 IV produced no significant changes in heart rate over time whilst at the same time it provided analgesia and sedation. Benzodiazepines were also excluded from the premedication regimen as pharmacodynamic interaction with neuroactive steroids has been reported (Harrison & Simmonds 1984; Visser et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although ketamine is frequently used in combination with diazepam, we chose xylazine and guaifenesin to provide muscle relaxation because of the reported acute functional adaptation to the EEG effect of the benzodiazepines in rats when administered a continuous infusion of alfaxalone (Visser et al. 2003).…”
Section: Discussionmentioning
confidence: 99%